'Here to Stay' – Tracing through health the development of New Zealand as a Pacific Nation. Issue 2 (1st October 2014) - Park, Julie; Littleton, Judith
We use health research and demography as a window onto the process by which New Zealand became a South Pacific nation. The making of the nation is the other side of the coin to the making of citizens. Counting and categorization is an important part of that process and tracing that history of counting through health research from 1937 to 1990 is what we do here. Becoming a nation with Pacific peoples as part of its citizenry is integral to the political identity journey of New Zealand from being a Better Britain of the South (Belich 1996: 302) to being part of the Pacific.We focus at the level of the state and state-funded health research. Our data are the official reports of the Medical Research Council of New Zealand and research published mainly in the New Zealand Medical Journal along with census materials. This work is part of a broader ethnographic project on Transnational Pacific Health, which focused on the Cook Islands, Tuvalu and New Zealand. In this larger project we have researched Pacific people's active engagement with the health sector, particularly in relation to culturally accessible services (e.g., Dunsford et al. 2011), but that story is not represented here.